Perempuan dan Literasi Finansial dalam Rumah Tangga: Sintesis Literatur Gender dan Ekonomi - Wahyu Wibowo; Alda Fildza Amima; Mega Rahmawati; Ahmad Wildan Raikhana; Najma Arum S Lessy (Yayasan Literasi Sains Indonesia, 2026)
This study examines women’s financial literacy in the household context, highlighting women’s role as key economic agents in managing family finances. Financial literacy is viewed not just as a technical skill but as a social practice shaped by gender relations, cultural norms, and power structures within the household. Women often manage daily budgets, regulate routine expenses, and plan long-term needs, although strategic financial decisions such as investments are still dominated by men. The study finds that women’s financial literacy plays a critical role in enhancing household economic resilience, particularly in the face of economic shocks such as inflation and financial crises. Furthermore, good financial literacy enables women to manage family resources more efficiently, improving the family’s economic welfare and reducing social inequalities. The study also emphasizes the importance of policies that support women’s empowerment through inclusive financial education, to achieve gender equality in household financial management and encourage women’s economic participation in society.